"God Said, 'You're Hearing the Voice of the President'": Citizenship in The Trump Prophecy. Issue 3 (2nd July 2020) - Sheldon, Zachary
ABSTRACT: The film The Trump Prophecy, "based on a true story, " tells the story of a firefighter, Mark Taylor, who foresaw Donald Trump's ascendancy to the Presidency in a vision from God. This vision led to the establishment of a nationwide prayer movement for Trump during the 2016 election. This article examines this film in light of the connections between religious media, politics, and gender. I argue that The Trump Prophecy articulates a rhetorical model for citizenship that I call "Holy Passivity." This model encourages Christians to remain set apart and passive in mainstream political action while maintaining active roles in faith communities. The film's articulation of this perspective twists traditionally feminine notions of passivity to enable male encroachment upon such understandings of citizenship and civic participation.